Structural evolution mechanisms and design strategies of layered cathodes for sodium-ion batteries - Li Zhang; Jun Wang; Wenhai Ji; Nuria Tapia-Ruiz; Martin Winter; Jie Li (Next Energy)
Although lithium-ion batteries are successfully used in electronic devices and electric vehicles, the steadily increasing price of their raw materials and increasing anxiety about Li resources and reserves raise concerns about exploring cheaper and sustainable alternatives. Sodium-ion batteries are one of the most promising energy storage systems but still cannot replace the status of lithium-ion batteries. One challenge of commercialization of sodium-ion batteries is their cathode material. Inspired by layered LiTMO2 (TM = transition metal) as cathode materials for lithium-ion batteries, layered NaxTMO2 materials are investigated as cathode materials for sodium-ion batteries. Although layered NaxTMO2 materials show high theoretical capacities and operating voltage windows, their cycling stability and rate capability still need to be improved. The electrochemical behavior of layered NaxTMO2 materials is correlated to the extraction and insertion of Na atoms during charge and discharge accompanied by structural changes, respectively. Understanding these structural changes during cycling of layered NaxTMO2 materials may initiate strategies to improve their electrochemical performance. Thus, the correlation between composition, structure and synthesis of layered NaxTMO2 materials is discussed in the present paper. Besides, the structural changes during cycling of layered NaxTMO2 materials are summarized according to their crystal structure accompanied by varied stacking of TMO2 and NaO2 layers. Based on this structure information, strategies are introduced to optimize the electrochemical performance of layered NaxTMO2 using design of their bulk crystal structures, local configurations around TM atoms and surface structures.